Pelaporan Dana Sosial Islam dalam Akuntansi Syariah: Tinjauan Literatur Terfokus dan Pemetaan Global - Judijanto, Loso (Eastasouth Institute, 2025)
This study aims to map the development of literature on Islamic social fund reporting within the field of Islamic accounting through a bibliometric approach. The main focus is directed toward identifying research trends, author collaborations, and international networks formed in this area. The analysis employs reputable databases and the VOSviewer software to generate visualizations of author network maps and inter-country linkages. The findings reveal several authors who act as key connectors in the research network, as well as cross-country collaborations that are relatively divided into two major clusters: the first is a research network led by Indonesia with connections to Western countries, and the second is a network led by Malaysia with linkages to Asia and the Middle East. Practically, these findings can serve as a reference for improving the quality of Islamic social fund reporting through collaboration among researchers and policymakers. Theoretically, this study contributes by expanding the understanding of the intellectual structure of Islamic accounting. However, limitations regarding data sources and analytical methods indicate the need for further studies with broader coverage and multidisciplinary approaches.